UNLOCKING THE SECRET OF RESEARCH FRAMEWORK - Khairunesa Isa (Penerbit UTHM, 2024)
Welcome to the world of research! Whether you are a seasoned academic or a curious newcomer, this book is designed to help you navigate the complex and exciting landscape of research. From the basics of defining research and understanding its importance, to the intricacies of variable selection and literature review, this book will guide you through every step of the research process. Chapter One invites you to explore the boundless realm of research through an academic lens. With a masterful blend of dramatic and erudite language, this chapter serves as a portal into the intricate world of research. Chapter Two delves into the crucial role of variables in the realm of research. With variables as the fundamental building blocks of research, this chapter provides a comprehensive overview of the distinct types of variables, including their unique properties and characteristics. In Chapter Three, our voyage entails guiding you through the intricate construction of theoretical, conceptual, and research frameworks while equipping you with the ability to discern between quantitative and qualitative research methods. Chapter Four will embark on a quest to unveil the essence of literature review, elucidating its fundamental definition and purpose. We will also equip you with the necessary tools and strategies to undertake a meticulous review, while navigating through the labyrinth of common obstacles and potential pitfalls. Chapter Five stands at the threshold of innovation, illuminating the interplay between literature review and research. The intricate relationship between literature review and research is laid bare, as we delve into how literature review influences the formulation of research questions, objectives, hypotheses, and methodology. In totality, this publication endeavours to serve as a definitive and extensive handbook to research, intended to cater to researchers of all calibres, irrespective of their levels of expertise. Our aspiration is that this book will not only foster an unbridled enthusiasm for the research journey but also enable you to produce seminal research output that advances your field of study.